Sustainability Reporting at Private Universities - Nadia Fathurrahmi Lawita; Siti Samsiah (Akuntansi & Ekonomika, 2018)
This research discusses sustainability reporting in the form of annual reports on private universities. Sustainability reporting is an entity report that not only presents the entity's financial information, but also provides information about its social and environmental activities. For private universities, sustainability reporting is very useful especially for presenting information to prospective students, society, Government as supervisors, as well as graduate users. This research uses a descriptive qualitative approach by acquiring information through University websites, media publications and social activities. Currently, sustainability reporting in private universities is still presented in the form of academic reports reported to university databases at the Ministry of Research, Technology and Higher Education of the Republic of Indonesia (Kemenristekdikti). Yet if only the annual report were prepared like a public company that discloses its information of higher education, it would become the main attraction for the community, especially prospective students in choosing universities and stakeholders as graduate users. To provide information needed by stakeholders as a form of transparency and accountability, private universities should present information in the form of annual reports describing financial performance as well as non-financial performance containing economic, environmental, social and spiritual aspects.